Benefits of biological nitrification inhibition of Leymus chinensis under alkaline stress: the regulatory function of ammonium-N exceeds its nutritional function - Wang, Gui; Zhang, Lihui; Guo, Zihan; Shi, Dongfang; Zhai, Huiliang; Yao, Yuan; Yang, Tianxue; Xin, Shuquan; Cui, Haiying; Li, Junqin; Ma, Jianying; Sun, Wei (Frontiers in Plant Science, 2023)
The production of root exudates with biological nitrification inhibition (BNI) effects is a strategy adopted by ammonium-N (NH4+-N) tolerant plant species that occur in N-limited environments. Most knowledge on BNI comes from plant species that occur in acidic soils. Here, combining field sampling and laboratory culture, we assessed the BNI-capacity of Leymus chinensis, a dominant grass species in alkaline grasslands in eastern Asia, and explored why L. chinensis has BNI ability. The results showed that L. chinensis has strong BNI-capacity. At a concentration of 1 mg mL-1, L. chinensis’ root exudates inhibited nitrification in soils influenced by Puccinellia tenuiflora by 72.44%, while DCD only inhibited it by 68.29%. The nitrification potential of the soil of L. chinensis community was only 53% of the P. tenuiflora community or 41% of the Suaeda salsa community. We also showed that the supply of NH4+-N driven by L. chinensis’ BNI can meet its requirements. In addition, NH4+-N can enhance plant adaptation to alkaline stress by regulating pH, and in turn, the uptake of nitrate-N (NO3–N). We further demonstrated that the regulatory function of NH4+-N is greater than its nutritional function in alkaline environment. The results offer novel insights into how L. chinensis adapts to high pH and nutrient deficiency stress by secreting BNIs, and reveal, for the first time, differences in the functional roles of NH4+-N and NO3–N in growth and adaptation under alkaline conditions in a grass species.